A conformal mapping approach to broadband nonlinear optics on chip - Huang, Chunyu (2024)
Integrated nonlinear optical devices play an important role in modern optical communications; however, conventional on-chip optical devices with homogeneous or periodic translation dimensions generally have limited bandwidth when applied to nonlinear optical applications. So far there lacks a general method to design compact nonlinear optical devices capable of operating over a broadband continuous frequency range. In this work we propose a general strategy based on transformation optics to design curved accelerating waveguides with spatially gradient curvatures, which can achieve broadband nonlinear frequency conversion on chip. Through rigorous analytical calculation, we show that increasing the acceleration (that is, the gradient in the waveguide curvature) broadens the output signal spectrum in the nonlinear process. In this experiment we use sum-frequency generation for infrared signal upconversion as an example and fabricated a variety of curved accelerating waveguides using thin-film lithium niobate on insulators. Efficient sum-frequency generation is observed over a broadband continuous spectrum. Our conformal mapping approach offers a platform for various nonlinear optical processes and works in any frequency range, including visible, infrared and terahertz bands. Apart from lithium niobate on insulators, our approach is also compatible with other nonlinear materials such as silicon, silicon nitride and chalcogenide glasses and so on.